2008
DOI: 10.1021/la802015f
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Behavior of Aluminum Oxide Nanoparticles As Affected by pH and Natural Organic Matter

Abstract: The colloidal behavior of aluminum oxide nanoparticles (NPs) was investigated as a function of pH and in the presence of two structurally different humic acids (HAs), Aldrich HA (AHA) and the seventh HA fraction extracted from Amherst peat soil (HA7). Dynamic light scattering (DLS) and atomic force microscopy (AFM) were employed to determine the colloidal behavior of the NPs. Influence of pH and HAs on the surface charges of the NPs was determined. zeta-Potential data clearly showed that the surface charge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 28 publications
11
111
2
6
Order By: Relevance
“…Steric hindrance effects may also contribute to the enhanced stability of humiccoated NPs. Conversely, Ghosh and co-workers [63] showed that at low pH, humic acid caused aggregation of Al 2 O 3 NPs. Here, the charge of the humic acid appeared sufficiently low to allow its aggregation because of hydrophobic interactions; thus, humic acid-coated particles also became susceptible to aggregation.…”
Section: Soil Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Steric hindrance effects may also contribute to the enhanced stability of humiccoated NPs. Conversely, Ghosh and co-workers [63] showed that at low pH, humic acid caused aggregation of Al 2 O 3 NPs. Here, the charge of the humic acid appeared sufficiently low to allow its aggregation because of hydrophobic interactions; thus, humic acid-coated particles also became susceptible to aggregation.…”
Section: Soil Propertiesmentioning
confidence: 97%
“…This sorption may influence particle properties in a number of ways. Humic substances are negatively charged at environmental pHs, and thus their sorption will make the overall particle-humic conglomerate negatively charged [63]. This may increase particle stability in solution, reducing aggregation and settling [48,61].…”
Section: Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In asymmetric bridging the polymer first attaches to one of the surfaces, leading to a modification in polymer configuration and entropy, which enables it to attach to the other particle it may otherwise not have interacted with [142]. Although studies of asymmetric bridging in NPs-based systems are sparse, factors affecting morphology of polymers such as pH, ionic strength, and temperature [144][145][146] are expected to affect heteroaggregation occurring via polymer bridging. Heteroaggregation via bridging may also refer to a phenomenon where a NPs connects to at least two other NPs (both similar) in a sandwich-like manner [147].…”
Section: Bridgingmentioning
confidence: 99%
“…In natural aqueous media, large NP agglomerates will deposit faster than single particles due to their gravity, and will be blocked easily while transporting into a porous media (Chen and Elimelech, 2007;Ghosh et al, 2008;Petosa et al, 2010). NPs interact with natural organic matter (NOM) under various chemical solutions, which controls the agglomeration of NPs, as well as their attachment to environmental surfaces (Keller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%